School Digitalization: Evaluation Program in Sekolah Penggerak at Samarinda City: Digitalisasi Sekolah: Evaluasi Program pada Sekolah Penggerak di Kota Samarinda - Diah Ambarfatih, Chindy; Rahmi Haerani, Rosita Putri; Khotimah, Khusnul; Trees Sandy, Aisyah (Borneo Educational Journal (Borju), 2025)
Digitalization in education seeks to enhance the effectiveness of dynamic education, aligning with one of the driving school interventions: school digitalization. The sekolah penggerak program, implemented for four years, is a government effort to improve the quality of education in Indonesia. Since the implementation of school digitalization, the learning quality data in the sekolah penggerak education report has been labeled “medium” with an average achievement score of 58.02. Furthermore, there has been a general decline in the quality of learning since 2023 in elementary school units, as evidenced by the Samarinda City education report card for 2024. Therefore, it is imperative to evaluate the school digitalization intervention program. The research methodology employed is program evaluation using the CIPP model. The population of this study consisted of the 10 first-generation sekolah penggerak program. The willing participants in this research were 7 schools, with informants comprising 7 school principals, 7 lower-class teachers, and 14 upper-class teachers. The research findings revealed that the program was largely aligned with the government’s targets. However, several obstacles were identified. Notably, the provision of facilities and infrastructure was incomplete, and some educators lacked the necessary competency in digital education.